Association of clinical features, comorbidities and laboratory profile with outcomes among dengue patients admitted in a tertiary care hospital, Delhi NCR - Tiwari, Mohit; Tibrewal, Abhishek; Pichika, Varun S.; Singh, Narinder P.; Choudhary, Pankaj N.; Agarwal, Rajat K. (International Journal of Research in Medical Sciences, 2021)
Background: Dengue fever is an endemic disease across multiple countries. Dengue infection results in a wide spectrum of non-specific clinical manifestations with unpredictable clinical course and outcome. Objective of the study was to understand the association of different clinical features, comorbidities and laboratory profile with outcomes (ICU use, ventilation use and blood transfusion) among dengue patients admitted in a tertiary care hospital in Delhi, National Capital Region. Methods This cross-sectional study included 75 dengue patients with fever <1 week confirmed based on NS-1 antigen and/or IgM antibody positivity. Descriptive analysis was used. Results: Gender was not significantly associated with the outcomes. The duration of fever was significantly higher among those with ICU use (median: 6 versus 4 days; p=0.005), ventilator use (median: 5.5 versus 4.0 days; p=0.049] and blood transfusion (median: 6 versus 4 days; p=0.013). Dengue patients with co-morbidities (diabetes, hypertension, or chronic obstructive pulmonary disease) or co-infection had a significantly higher odds of the outcomes. The platelet level was significantly lower while liver enzymes were significantly higher among those with the outcomes. Conclusions: The clinical features, comorbidities and laboratory profile can help in identifying critical patients for ICU admission and timely intervention to improve outcome.